AGAMA SEBAGAI FONDASI PERKEMBANGAN MASYARAKAT DAN PERUBAHAN SOSIAL: STUDI KASUS ORANG HATUHAHA DI NEGERI PELAUW MALUKU TENGAH - Yance Z. Rumahuru (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
This paper analyses the issues of religion and social change, whether religion influences the changes in the life of communities. It aims at revealing the role of religion in the development of changes in Muslim community, especially that of Hatuhaha in Pelauw Central Moluccas. This paper is based on the fieldwork in Pelauw, Pulau Haruku, Central Maluku, using the historical-anthropological approach of qualitative method. The research found that religion (Islam) has become an important strength of the development of community and social change in Pelauw.